People's Republic of China : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2005 Article IV Consultation on the People's Republic of China highlights economic developments, policy discussions, and structural reforms. A larger external current account surplus, together with strong capital inflows, led to a further sizable increase in gross official reserves. A disorderly unwinding of global current account imbalances would also threaten China's growth, as economic activity in all countries would likely suffer lingering adverse effects. Executive Directors commended the authorities for the success in sustaining high economic growth rates and for their efforts to guide the economy.